ASSESSING ECOLOGICAL HEALTH: THE IMPACT OF HEAVY METAL CONTAMINATION IN LUHU DAM, ADAMAWA STATE - Abasiryu, Apagu; Bamaiyi, Chaka; Mshelia, Mbilari B.; Musa, Mohammed; E. Hassan, Inuwa; Ngati, Filibus (FUDMA Journal of Sciences, 2026)
Water is an essential resource covering 75% of Earth's surface, providing habitat for various organisms and facilitating gas exchange and nutrient transport. However, human activities around Luhu Dam in the Michika Local Government Area of Adamawa State, Nigeria, have increased the presence of heavy metals, which pose significant ecological threats due to bioaccumulation and biomagnification. This study aimed to assess the concentrations of seven heavy metals-iron (Fe), zinc (Zn), cadmium (Cd), lead (Pb), chromium (Cr), manganese (Mn), and copper (Cu)-in the surface water and sediments of Luhu Dam over six months (July 2025 to January 2026). Water and sediment samples were collected biweekly from three stations and analyzed using Atomic Absorption Spectrophotometry. The results revealed distinct spatial variations in metal concentrations. In water samples, significant differences in cadmium (0.01-0.04 mg/l) and manganese (0.057-0.166 mg/l) were observed (p
Keywords: Heavy metals; water quality; sediment contamination; Luhu Dam; pollution assessment; Adamawa State